Experimental Investigation of Engine Performance and Exhaust Emissions of DI Diesel Engine using various Water in Diesel Emulsion - Ngaing , Ing Kai (IRC, 2016)
The aim of this Final Year Project is to investigate the engine performance and exhaust emission of a Direct Injection (DI) diesel engine while using different water-in-diesel emulsions (WiDE). The WiDE that is used for this project is blended before the experiment to ensure the emulsion fuels are sufficiently stable for testing. Six different types of WiDE will be blended using the means of mechanical agitation. The WiDE is blended with two different HLB values. First is by preparing the WiDE with a HLB value of 6 and total volume of surfactant equal to 10% of water used. Then is the preparation of WiDE with a HLB value of 9 and total volume of surfactant equal to 15% of water used. WiDE with 9%, 12% and 15% water content is prepared with HLB values of 6 and 9, which would result in a total of six emulsion fuels. The prepared WiDE is tested using Yanmar L100V single cylinder, direct injection compression-ignition engine. The experiment is run with engine speed of 2000RPM and varying engine loads from 0% increasing to 100%. Results on brake torque, brake power and brake specific fuel consumption is obtained using electric dynamometer, data acquisition system and engine test bed. The result regarding exhaust emission on the other hand is obtained using automotive emission analyzer and diesel smoke opacity meter. The relationships between the engine performances, exhaust emission and water-in-diesel emulsion fuels will be studied. For brake power, all WiDE shows positive effect as the brake power is higher when using WiDE compared with diesel. Brake specific fuel consumption (BSFC) on the other hand, at 10% engine load, all WiDE with HLB 6 shows higher BSFC while all WiDE with HLB 9 shows lower BSFC compared with BSFC of diesel. The result shows significant reduction in nitrogen oxides (NOx) emission and smoke opacity when running the engine with WiDE. Carbon dioxide (CO2), carbon monoxide (CO) and oxygen (O2) emission is dependent on the combustion temperature.